Early Postischemic Cerebral Circulatory Disorders and Their Correction with Perftoran - V. V. Aleksandrin; V. L. Kozhura; I. S. Novoderzhkina; V. V. Moroz (Общая реаниматология, 2006)
Objective: to study the conditions and mechanism of postischemic no-reflow and delayed hypoperfusion and to correct them with perfluorane.Materials and methods: Both phenomena were reproduced by using a rat model of global cerebral ischemia.Results: no-reflow was shown to be caused by pial arteriolar collapse that occurred in ischemia and lasted during reperfusion. Delayed postischemic hypoperfusion was induced by increased pial arteriolar tone.Conclusion: Intraarterial injection of perfluorane alleviates the manifestation of both phenomena due to better oxygen supply to ischemic brain tissue and, probably, to calcium channel blockage.